2015
DOI: 10.1084/jem.20141898
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Tifab, a del(5q) MDS gene, alters hematopoiesis through derepression of Toll-like receptor–TRAF6 signaling

Abstract: Varney et al. report that that deletion of the TRAF-interacting protein TIFAB contributes to an MDS-like phenotype in mice by up-regulating TRAF6 and contributing to hematopoietic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 53 publications
6
100
1
Order By: Relevance
“…However, in the instance of progressive BM failure, this argument is not very compelling, because our data indicate that HSC destruction in miR-146a −/− mice is driven by aberrantly activated T cells; therefore, it is not obvious why Traf6 haploinsufficiency, while having a profound effect on other T cell-dependent defects in miR-146a −/− mice, would have little impact on BM failure. Of note, our conclusion on the role of Traf6 runs contrary to some observations that implicated this adapter molecule in the regulation of HSC homeostasis and the pathophysiology of MDS (10,41,42).…”
Section: Traf6contrasting
confidence: 99%
“…However, in the instance of progressive BM failure, this argument is not very compelling, because our data indicate that HSC destruction in miR-146a −/− mice is driven by aberrantly activated T cells; therefore, it is not obvious why Traf6 haploinsufficiency, while having a profound effect on other T cell-dependent defects in miR-146a −/− mice, would have little impact on BM failure. Of note, our conclusion on the role of Traf6 runs contrary to some observations that implicated this adapter molecule in the regulation of HSC homeostasis and the pathophysiology of MDS (10,41,42).…”
Section: Traf6contrasting
confidence: 99%
“…18,19 This is attributed to haploinsufficiency for critical 5q gene(s), which in cooperation with additional signaling networks, drives malignant transformation and clonal evolution in these disorders. [20][21][22] In keeping with this, treatments that are effective in 5q-deleted myeloid malignancies have been shown to directly target critical haploinsufficient 5q genes and their signaling networks. 20 Based on the latter findings, [20][21][22] we hypothesized that similar 5q gene haploinsufficiency mechanisms are likely to operate in BPDCN and that identification of the relevant 5q target genes might lead to new insight into disease biology and therapy.…”
Section: Introductionmentioning
confidence: 92%
“…[20][21][22] In keeping with this, treatments that are effective in 5q-deleted myeloid malignancies have been shown to directly target critical haploinsufficient 5q genes and their signaling networks. 20 Based on the latter findings, [20][21][22] we hypothesized that similar 5q gene haploinsufficiency mechanisms are likely to operate in BPDCN and that identification of the relevant 5q target genes might lead to new insight into disease biology and therapy. In this setting, we have used molecular cloning coupled with molecular cytogenetics and next-generation sequencing to characterize 5q alterations in BPDCN.…”
Section: Introductionmentioning
confidence: 92%
“…7,19 All I-5q had a CDR at band 5q31 ( Figure 1A), encompassing the 1 Mb CDR of high-risk myelodysplastic syndrome/acute myeloid leukemia del(5q). 3,4,20 When we compared I-5q-positive cases with T-5q and T-ALL without del(5q), we found that the expression levels of IRF1, EGR1, CTNNA1, HNRNPAO, TIFAB, and CXXC5, known putative onco-suppressors in in vitro and/or in vivo models [20][21][22][23][24] mapping within the CDR, did not differ between the three groups; while the presence of I-5q was associated with significant down-regulation of NR3C1 and TCF7 genes ( Figure 1B, Online Supplementary Information and Online Supplementary Figures S2 and S3).…”
Section: Interstitial 5q T-cell Acute Lymphoblastic Leukemiamentioning
confidence: 99%